2017
DOI: 10.1063/1.4973992
|View full text |Cite
|
Sign up to set email alerts
|

Localized tail state distribution and hopping transport in ultrathin zinc-tin-oxide thin film transistor

Abstract: Carrier transport properties of solution processed ultra thin (4 nm) zinc-tin oxide (ZTO) thin film transistor are investigated based on its transfer characteristics measured at the temperature ranging from 310 K to 77 K. As temperature decreases, the transfer curves show a parellel shift toward more postive voltages. The conduction mechanism of ultra-thin ZTO film and its connection to the density of band tail states have been substantiated by two approaches, including fitting logarithm drain current (log ID)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The localized states are filled as the charge density is increased after which the transport transitions to high mobility band transport so that ntr is a measure of the defect state density. This process has been observed in 2D semiconductors [35] and it contributes to the subthreshold rise in thin film transistors [36].…”
Section: Gate Voltage [V]mentioning
confidence: 82%
“…The localized states are filled as the charge density is increased after which the transport transitions to high mobility band transport so that ntr is a measure of the defect state density. This process has been observed in 2D semiconductors [35] and it contributes to the subthreshold rise in thin film transistors [36].…”
Section: Gate Voltage [V]mentioning
confidence: 82%
“…It is inferred that because the reaction of oxygen vacancies formation becomes more intense at high temperature (above 650 K), the concentration of oxygen vacancy increases significantly and the LAO/STO heterojunction is in an oxygen vacancies-rich state, which increases the system disorder degree and generates band-tail states at the bottom of the conduction band [22]. As shown in figure 3(b), electrons are thermally excited from the defect levels to a band-tail state first and then contribute to conductivity by jumping between band-tail states [22]. In this case, the conduction mechanism of LAO/STO heterojunction transferred to constant range hopping conduction.…”
Section: E D (Ev)mentioning
confidence: 99%
“…Also, tail-states near the conduction band edge in the amorphous OS channels causes non-sharp change in the density of states (DOS), which degrades the subthreshold characteristics of the TFET [3]. Furthermore, it has been reported that a thin ZnSnO layer can include a high density of localized tail-states below E c [37]. Electrons trapped into the localized tail states in ZnSnO or other amorphous OS materials cannot directly flow in the OS channels [27], [38], but can contribute to the channel conduction by thermal activation into states higher than the mobility edge as shown in Fig.…”
Section: Physical Factors To Limit Sub-threshold Characteristics Omentioning
confidence: 99%